2017
DOI: 10.1038/nn.4589
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of missense mutation identify neurodevelopmental disorder genes and functional domains

Abstract: Although de novo missense mutations have been predicted to account for more cases of autism than gene-truncating mutations, most research has focused on the latter. We identified the properties of de novo missense mutations in patients with neurodevelopmental disorders (NDDs) and highlight 35 genes with excess missense mutations. Additionally, 40 amino acid sites were recurrently mutated in 36 genes, and targeted sequencing of 20 sites in 17,689 NDD patients identified 21 new patients with identical missense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
178
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 81 publications
(105 reference statements)
6
178
0
Order By: Relevance
“…Moreover, until now, novel gene discovery in epilepsy has largely focused on truncating variants, partly because these variants are easier to interpret in the context of a haploinsufficient model. However, in accordance with a recent study that included molecular data from patients 6 and 9, the present study emphasizes the importance of recurrent missense variation in neurodevelopmental disorders, including intellectual disability and epilepsy 26 . This observation has also been illustrated in the epilepsies in a recent study that identified a recurrent missense mutation in a more common epilepsy gene, SCN1A , that produced a profound phenotype, far more severe than the well-established Dravet syndrome presentation of this gene 7 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, until now, novel gene discovery in epilepsy has largely focused on truncating variants, partly because these variants are easier to interpret in the context of a haploinsufficient model. However, in accordance with a recent study that included molecular data from patients 6 and 9, the present study emphasizes the importance of recurrent missense variation in neurodevelopmental disorders, including intellectual disability and epilepsy 26 . This observation has also been illustrated in the epilepsies in a recent study that identified a recurrent missense mutation in a more common epilepsy gene, SCN1A , that produced a profound phenotype, far more severe than the well-established Dravet syndrome presentation of this gene 7 .…”
Section: Discussionsupporting
confidence: 89%
“…However, in accord with a recent study that included molecular data from patients 6 and 9, the present study emphasizes the importance of recurrent missense variation in neurodevelopmental disorders, including intellectual disability and epilepsy. 26 This observation has also been illustrated in the epilepsies in a recent study that identified a recurrent missense mutation in a more common epilepsy gene, SCN1A, that produced a profound phenotype, far more severe than the well-established Dravet syndrome presentation of this gene. 7 In addition, the role of missense mutations in DEE, and especially recurrent ones, has been emphasized in another recent article.…”
Section: Discussionmentioning
confidence: 84%
“…Loss of function of ITPR1 has been found by multiple groups to be a rare single gene cause of autism 106,[153][154][155][156] . This prompted Gargus and colleagues to look at functional deficits in IP3-mediated calcium signaling in primary skin fibroblasts from Fragile X patients as they represent a common syndromic cause of autism 157 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…[3][4][5][6] Similarly, largescale WES studies of individuals affected by ID/DD have recently leveraged this phenomenon as supporting evidence of the involvement of a gene in disease. 7,8 This spatial clustering of de novo mutations (DNMs) is typical for missense mutations in genes without clear, or limited numbers of, truncating mutations subsequently degraded by nonsense-mediated mRNA decay, suggesting that these clustered mutations act through a different mechanism than haploinsufficiency (HI).…”
mentioning
confidence: 90%
“…32,33 GABBR2 was very recently also reported by others to show significant de novo mutation clustering in a neurodevelopmental cohort. 6 Our method might potentially identify clustering based on identical mutations in multiple individuals only as a result of issues in the underlying cohort. It could for instance be that the same individual was included in multiple studies and therefore occurs twice in the cohort.…”
mentioning
confidence: 99%